Jews and the ends of theory - Ginsburg, Shai, 1967-; Land, Martin, 1953-; Boyarin, Jonathan (Fordham University Press, 2019)
"This volume assesses the role of Jews, as both agents and figures, in the development of critical and literary theory in the twentieth century and beyond. Its topics range from biblical criticism to the relationship between Derrida and Levinas, from Mizrachi Jews in Israel to the Zionisms of Buber and Scholem"--